2000
DOI: 10.1093/mutage/15.6.459
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome painting reveals specific patterns of chromosome occurrence in mitomycin C- and diethylstilboestrol-induced micronuclei

Abstract: Tucker, 1989) or by FISH with pan-centromeric DNA probes D-67653 Kaiserslautern, Germany (Becker et al., 1990, Miller et al., 1992. The drugs that have Cultures of human blood lymphocytes from three subjects been studied in most detail for their mechanism of MN were incubated with the clastogen mitomycin C (MMC, induction are the clastogen mitomycin C (MMC) (e.g. Miller 500 ng/ml) and the aneugen diethylstilboestrol (DES, and Adler, 1990;Miller et al., 1991; Rudd et al., 1991; 80 µM) 23 h before harvesting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 72 publications
7
27
0
Order By: Relevance
“…In our study, MMC generated a high MN and a low NDI in the CBMN assay and a high GDI and an increased percentage of damaged cells in the alkaline comet assay. These findings agree with other studies that showed mutagenic and clastogenic activity for MMC (Fauth et al, 2000;Krishnaja and Sharma, 2008;Sontakke and Fulzele, 2009). It has been reported that in vivo vanillin treatment decreased the MMC-induced MN ratio in the bone marrow of mice (Inouye et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, MMC generated a high MN and a low NDI in the CBMN assay and a high GDI and an increased percentage of damaged cells in the alkaline comet assay. These findings agree with other studies that showed mutagenic and clastogenic activity for MMC (Fauth et al, 2000;Krishnaja and Sharma, 2008;Sontakke and Fulzele, 2009). It has been reported that in vivo vanillin treatment decreased the MMC-induced MN ratio in the bone marrow of mice (Inouye et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…MMC is a highly genotoxic agent that induces chromosomal aberrations and sister chromatid exchanges in cultured human blood lymphocytes (Krishnaja and Sharma, 2008), increases MN frequency (Fauth et al, 2000) and induces higher MN formation in human liver fibroblast cultures (Nesti et al, 2000). In our study, MMC generated a high MN and a low NDI in the CBMN assay and a high GDI and an increased percentage of damaged cells in the alkaline comet assay.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, we used this antitumor-antibiotic drug to test the possible antimutagenic activity of concrete and absolute oils. The study results of MMC in this experiment were coincided with previous reports (Fauth et al 2000;Yogesh and Fulzele 2009;Unal et al 2013). The group treated with MMC alone showed a significant elevation of chromosomal damage.…”
Section: Gc-ms Analysissupporting
confidence: 92%
“…This would inhibit DNA replication and probably might be the antitumor action of this drug. Despite the fact that MMC showed antitumor action, many reports proved that it may cause high frequency of chromosomal aberrations, sister chromatid exchanges and micronuclei formation (Latt 1974;Fauth et al 2000;Yogesh and Fulzele 2009). In this study, we used this antitumor-antibiotic drug to test the possible antimutagenic activity of concrete and absolute oils.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…However, gene density and chromosome position in nuclei have a tendency of slightly influencing MMC-induced MN formation. The explanation for this tendency can be the exceptional high contribution in MN formation of chromosome 9 with low gene density and peripheral location in nuclei, caused by its high sensitivity to ММС (Fauth et al 2000). However, further studies are certainly needed to clarify the mechanisms of MN formation.…”
Section: Discussionmentioning
confidence: 99%